Interaction of Gene-Environmental in Attention Deficit/Hyperactivity Disorder (ADHD): The Importance from Developmental Perspectives - Yunias Setiawati (Perhimpunan Dokter Spesialis Kedokteran Jiwa Indonesia, 2017)
Attention deficit hyperactivity disorder (ADHD) is known as a neurodevelopmental disorder under genetic influences characterized by impairing attention, motor hyperactivity and impulsivity. ADHD often continues into adulthood and co-exist with other psychiatric and medical conditions. Although ADHD is characterized by the symptoms of attention deficit, hyperactivity, and impulsivity, it was reported that it might have an impact of environmental influences on the developmental course of the symptoms.